1999
DOI: 10.1046/j.1365-2311.1999.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between understorey and canopy in herbivore community composition and leaf quality for two oak species in Missouri

Abstract: Summary 1. From July 1994 to September 1995, at six censuses, the herbivore community associated with understorey (< 2.5 m height) and canopy (15–20 m) leaves of Quercus alba and Q. velutina was sampled in south‐eastern Missouri, U.S.A. 2. Across all censuses, herbivore densities were not significantly different between canopy and understorey for Q. alba and Q. velutina, except in August 1994 when herbivore densities were 60% higher in the canopy on Q. alba. Little significant spatial variation in herbivore de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 29 publications
3
79
2
1
Order By: Relevance
“…Other studies in oaks found the same results as Feeny (1970); they reported a negative relationship between the concentration of tannins in the plant and the abundance and richness of herbivores (leaf-chewing insects, leaf miners, and gall-forming) that inhabit the canopy of Q. alba, Q. velutina (Le Corff and Marquis 1999;Forkner et al 2004), Q. crispula (Murakami et al 2005(Murakami et al , 2008, Q. geminata, Q. laevis Stiling 2006, 2008), and Q. gambelii × Q. grisea (Yarnes et al 2008).…”
Section: Chemistry Of the Host Plantmentioning
confidence: 57%
“…Other studies in oaks found the same results as Feeny (1970); they reported a negative relationship between the concentration of tannins in the plant and the abundance and richness of herbivores (leaf-chewing insects, leaf miners, and gall-forming) that inhabit the canopy of Q. alba, Q. velutina (Le Corff and Marquis 1999;Forkner et al 2004), Q. crispula (Murakami et al 2005(Murakami et al , 2008, Q. geminata, Q. laevis Stiling 2006, 2008), and Q. gambelii × Q. grisea (Yarnes et al 2008).…”
Section: Chemistry Of the Host Plantmentioning
confidence: 57%
“…Variation in microclimatic conditions and resource quality might impede the diversity of Lepidoptera along a vertical gradient (Schulze, Linsenmair, & Fiedler, 2001). Due to its higher foliage quality, the understory of temperate forests harbors more species‐rich lepidopteran assemblages than the canopy (Hirao et al., 2009; Le Corff & Marquis, 1999). Therefore, the higher diversity recorded in the first level might be due to the involvement of understory species, supporting our original hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we expect density, diversity, and parasitism rates to decrease from the first toward the third canopy level, due to harsher abiotic conditions and lower foliage quality toward the upper canopy (Hirao, Murakami, & Kashizaki, 2009; Le Corff & Marquis, 1999). Moreover, in temperate forests, the understory contributes to lepidopteran diversity more than the canopy (Hirao et al., 2009; Le Corff & Marquis, 1999), with canopy and understory assemblages potentially sharing many species (Hirao et al., 2009). Therefore, we also expect an increased involvement of understory species in the first canopy level, leading to an increase in their density and diversity, and, consequently, parasitoid density and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, on Quercus spp. in the USA, more leaf-chewing species fed on sapling than on conspecific trees, and none were restricted to the canopy (Le Corff and Marquis 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Fowler 1985;Schowalter and Ganio 1998;Le Corff and Marquis 1999). In tropical rainforests, many abiotic and biotic characteristics of the upper canopy (the uppermost leaf layer) are different from those of lower forest layers.…”
Section: Introductionmentioning
confidence: 99%